Effect of Different Levels of Protein and Protexin on Broiler Performance - Mehr, M. Azadegan; Shargh, M. Shams; Dastar, B.; Hassani, S.; Akbari, M.R. (International Journal of Poultry Science, 2007)
A feeding trail was conducted to evaluate the effects of different levels of dietary protein and protexin (a commercial probiotic compound) on broiler performance. In a completely randomized design with 2 x 3 factorial arrangement, 360 male broiler chicks were divided into 24 groups, 15 chicks per. Treatments consisted of combination of two levels of protein (NRC and 90% of NRC) and three levels of protexin (without protexin, the recommended level and 120% of recommended level). All of the diets were formulated according to the NRC tables except for protein. Protexin significantly (P<0.05) increased weight gain in growing as well as the whole production period. Feeding protexin at 120% of the recommended level caused a significant improvement in feed conversion ratio compared to the control group. Protexin had no significant effect on feed consumption, carcass percentage, abdominal fat and the cost of consumed feed. Decreasing dietary protein caused a significant decrease in feed cost (P<0.05). Inclusion of protexin into diet at 120% of the recommended level significantly (P<0.05) decreased feed cost per kilogram of live weight gain.